An innovative compact system for advanced treatment of combined sewer overflows (CSOs) discharged into large lakes: Pilot-scale validation. (15th February 2020) - Botturi, A.; Daneshgar, S.; Cordioli, A.; Foglia, A.; Eusebi, A.L.; Fatone, F.
Abstract: Combined sewer overflows discharging into natural water bodies could potentially contaminate them in terms of conventional wastewater parameters and coliform bacteria. When green water infrastructures are not technically feasible or practically sustainable for stormwater management, innovative compact and effective end-of-pipe systems can be of interest. This study presents long-term and real-environment validated data of a compact and rapid treatment system specifically applicable to CSOs that consists of a dynamic rotating belt filter, adsorption on granular activated carbon and UV disinfection steps. The results of treatment for Lake Garda in Italy, showed great potential for TSS, COD and E. coli removal efficiencies with more than 90%, 69% and 99% respectively. Due to the short contact time of GAC adsorption, nutrients removals were not very high. TN and TP removal of around 41% and 19% were observed respectively that suggests further specific nutrients removal processes are required for achieving higher efficiencies. The treatment system, due to its compactness and rapidness could be a great asset for water utilities in different EU catchments that are dealing with the frequent CSO events. In addition, the possibility of using different combinations of treatment steps allows the choice of different treatment scenarios depending on the treatment goals for any specific catchment. Graphical abstract: Image 104368 Highlights: The concern about CSOs contamination in natural water bodies is increasing. An innovative treatment system has been implemented for combined sewer overflows. High TSS and COD removal is achievable through filtration and adsorption. E. coli is almost completely removed out of the system using UV disinfection. Compactness, modularity and efficiency are innovative aspects of treatment system.